Developing Halal-related Courses for Students Majoring in Culinary Arts Program in Private Institutions - Munlum, Satitpong (Dusit Thani College Journal, 2020)
The research aimed were investigate the desired characteristics of graduates for Halal-certified workplace and develop Halal related courses in the culinary arts program. Qualitative research was applied to the executives from Halal-certified workplace and experts, while the questionnaire was used with the samples who were the students majoring in Culinary Arts Program from 3 private institutions: Dusit Thani College, Ratanabandit University and Rangsit University. The findings revealed that employers in the workplace required that graduates who entered their employment at first would have impressive characteristics, being polite, tidy, respecting others, smiling, able to provide good service to satisfy their customers and create a good image for the organization which could be accepted and trusted by the customers. Therefore, the role of the institutions in improving the curriculum should be consistent with expectation of the workplace, providing appropriate teaching equipment for cooking classes based on Halal principles in Islam, creating a good learning atmosphere and having evaluations in line with the curriculum.